Heterogeneity in the spatial distribution of bacterial sexually transmitted infections - Schleihauf, E.; Watkins, Rochelle; Plant, Aileen (BMJ Publishing Group, 2009)
Objectives: Detailed knowledge of the spatial distribution of disease is required to inform service delivery and plan effective interventions. In order to elucidate the spatial epidemiology of three common sexually transmitted infections (STI) further, any significant spatiotemporal clustering of gonorrhoea, chlamydia or syphilis cases in New South Wales (NSW) was detected and described. Methods: Eleven years of notified STI case data were analysed. Calculation of age and sex-stratified incidence rates was followed by spatiotemporal cluster analyses to investigate differences in the epidemiology of gonorrhoea, chlamydia and syphilis. Results: More than one-third of all gonorrhoea, chlamydia and syphilis cases in NSW were detected within cluster areas. Gonorrhoea cases were the most highly clustered, followed by syphilis, then chlamydia. Clusters were highly significant and relative risk estimates ranged from 1.6 to 22.9. Conclusion: The findings establish the high degree of geographical heterogeneity in STI incidence in NSW and indicate that the postal area of residence is an important predictor of STI incidence. Geographical surveillance could be incorporated into routine STI surveillance to identify populations in need of intervention. The evidence presented in this report indicates a need to implement geography-specific and phase-appropriate STI prevention and control strategies.